Μια Νέα Εποχή για το Ελληνικό Επιστημονικό Περιοδικό «ΑΚΤΙΝΟΤΕΧΝΟΛΟΓΙΑ» - Γεωργιάδης Κωνσταντίνος; Δρακουλίδου Στέλλα; Malamateniou, Christina; Κωνσταντινίδης Κλεάνθης (Ακτινοτεχνολογία, 2024)
Δεν υπάρχει διαθέσιμη περίληψη